2021
DOI: 10.3390/buildings11040158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coarse Aggregate Maximum Size on Synthetic/Steel Fiber Reinforced Concrete Performance with Different Fiber Parameters

Abstract: Recently, fiber has been incorporated into concrete mixtures, where its distribution in the concrete matrix helps to improve and enhance the mechanical properties of fiber-reinforced concrete (FRC). The aim of this study is to investigate the influence of steel and synthetic fiber parameters, along with different coarse aggregate maximum sizes (CAMZs) on FRC performance. Additionally, in past research, the empirical relationships among the compressive, tensile, and flexural strengths of plain concrete and FRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The better performance of 12.5 mm granite concrete may be due to the ease of compaction of smaller-sized aggregate concrete while the optimal behaviour of concrete made with blended aggregates may be attributed to the presence of medium-sized aggregates where some voids are filled in the interfacial transition zone (ITZ) which Wei et al, (2020) reported is responsible for higher strength gain. Also, the higher compressive strength attained with concrete containing smaller granite size aligns with reports of some researches (Umasabor & Osayogie, 2020;Al-baghdadi et al, 2021). Concrete specimens showed reduced residual strength with increment in heating temperature as presented in Figure 3 and Table 3.…”
Section: Compressive Strength Behaviour Before and After Heatingsupporting
confidence: 88%
“…The better performance of 12.5 mm granite concrete may be due to the ease of compaction of smaller-sized aggregate concrete while the optimal behaviour of concrete made with blended aggregates may be attributed to the presence of medium-sized aggregates where some voids are filled in the interfacial transition zone (ITZ) which Wei et al, (2020) reported is responsible for higher strength gain. Also, the higher compressive strength attained with concrete containing smaller granite size aligns with reports of some researches (Umasabor & Osayogie, 2020;Al-baghdadi et al, 2021). Concrete specimens showed reduced residual strength with increment in heating temperature as presented in Figure 3 and Table 3.…”
Section: Compressive Strength Behaviour Before and After Heatingsupporting
confidence: 88%
“…Splitting strength and flexural strength tests were performed, following ASTM C496/C496M-17 [27] and ASTM C78/C78M-18 [28], as shown in Figure 3. As reported in past research [24,[29][30][31], the MSSF reduces the brittleness and increases the ductility of FRC, as listed in Table 3. In this table, brittleness ratios were calculated for both mixes by dividing the compressive to flexural strength.…”
Section: Design and Materials Propertiessupporting
confidence: 60%
“…Ordinary Portland cement was used. Based on previous research findings and recommendations, the MSSF content of 1.5% was added to the concrete mixture [15,24]. This fiber has a length of 13 mm with a nominal tensile strength of more than 2100 MPa provided by the manufacturer (see Figure 2).…”
Section: Design and Materials Propertiesmentioning
confidence: 99%
“…The SFRC mixes containing hooked ISF and their 28-day CS (tested by 150 mm cubic samples) were collected from the literature 11 , 13 , 21 33 . Some of the mixes were eliminated due to comprising recycled steel fibers or the other types of ISFs (such as smooth and wavy).…”
Section: Methodsmentioning
confidence: 99%